Modulation of adrenergic receptors and adrenergic functions in cold adapted humans - Janský, Ladislav; Vybíral, Stanislav; Trubacová, Miloslava; Okrouhlík, Jan (European journal of applied physiology, 2008)
To specify the role of adrenoceptors in mediating adrenergic functions after adaptation of humans to cold, effect of administration of increasing concentrations of beta1 and beta2 adrenomimetics (Dobutamine, Bricanyl) on resting metabolic rate, heart rate, systolic blood pressure, rectal and skin temperatures of control humans and of cold adapted winter swimmers was studied. Increase in metabolic rate, mediated by beta1 and beta2 adrenomimetics, was attenuated after cold adaptation, indicating downregulation of beta1 and beta2 adrenoceptors. Since cold adapted humans have greater capacity of nonshivering thermogenesis, than that mediated by both beta1 and beta2 adrenoceptors, the role of other subtypes of adrenoceptors in mediating nonshivering thermogenesis is anticipated. Heart rate increased after administration of the beta2 agonist, but was not influenced by the beta1 agonist. The significance of beta2 adrenoceptors in mediating heart rate was depressed after cold adaptation. Data indicate that modifications of activity of beta adrenoceptors play crucial role in mechanisms responsible for adaptation of humans to cold.
Keywords: dobutamin; terbutalin; Receptors, Adrenergic, beta-2; Humans; Skin Temperature; Swimming; Oxygen Consumption; Adaptation, Physiological; termogeneze; Female; dospělí; nízká teplota; Heart Rate; sympatický nervový systém; lidé; Receptors, Adrenergic, beta-1; metabolismus; agonisté beta-2-adrenergních receptorů; Cold Temperature; Adrenergic beta-Agonists; Adrenergic beta-2 Receptor Agonists; Adult; teplota kůže; Dobutamine; Terbutaline; ženské pohlaví; Metabolism; krevní tlak; Male; srdeční frekvence; agonisté beta-1-adrenergních receptorů; adrenergní receptory; spotřeba kyslíku; Infusions, Intravenous; agonisté adrenergních beta-receptorů; fyziologická adaptace; beta-1-adrenergní receptory; Adrenergic beta-1 Receptor Agonists; Thermogenesis; Receptors, Adrenergic; mužské pohlaví; Sympathetic Nervous System; plavání; Blood Pressure; intravenózní infuze; beta-2-adrenergní receptory